2000
DOI: 10.1016/s0378-1097(00)00372-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival of free DNA encoding antibiotic resistance from transgenic maize and the transformation activity of DNA in ovine saliva, ovine rumen fluid and silage effluent

Abstract: To assess the likelihood that the bla gene present in a transgenic maize line may transfer from plant material to the microflora associated with animal feeds, we have examined the survival of free DNA in maize silage effluent, ovine rumen fluid and ovine saliva. Plasmid DNA that had previously been exposed to freshly sampled ovine saliva was capable of transforming competent Escherichia coli cells to ampicillin resistance even after 24 h, implying that DNA released from the diet could provide a source of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…Several bacterial species with the potential to develop competence belong to the common gut microbial community In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Duggan et al, 2000(Duggan et al, , 2003Mercer et al, 1999aMercer et al, , 1999bMercer et al, , 2001. to take up and recombine extracellular DNA.…”
Section: Exposure Characterisationmentioning
confidence: 99%
“…Several bacterial species with the potential to develop competence belong to the common gut microbial community In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Duggan et al, 2000(Duggan et al, , 2003Mercer et al, 1999aMercer et al, , 1999bMercer et al, , 2001. to take up and recombine extracellular DNA.…”
Section: Exposure Characterisationmentioning
confidence: 99%
“…However, competence development and transformation of such bacteria with genomic DNA of plants has not been observed in the lower gastrointestinal tract even with optimised model systems providing a selective advantage (Nordgård et al, 2007;EFSA, 2009a;Rizzi et al, 2012). In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Duggan et al, 2000(Duggan et al, , 2003Mercer et al, 1999aMercer et al, ,b, 2001Rizzi et al, 2012). Once the recombinant DNA is taken up, it must integrate into the recipient genome to persist during host replication.…”
Section: Plant To Bacteria Gene Transfer and Its Consequences 38mentioning
confidence: 99%
“…Several bacterial species with the potential to develop competence belong to the common gut microbial community (EFSA, 2009;Rizzi et al, 2011). In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Duggan et al, 2000(Duggan et al, , 2003Mercer et al, 1999aMercer et al, , 1999bMercer et al, , 2001. In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Duggan et al, 2000(Duggan et al, , 2003Mercer et al, 1999aMercer et al, , 1999bMercer et al, , 2001.…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%